2017
DOI: 10.1186/s12966-017-0579-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Supporting Physical Activity in the Childcare Environment (SPACE) intervention on preschoolers’ physical activity levels and sedentary time: a single-blind cluster randomized controlled trial

Abstract: BackgroundPhysical activity levels among preschoolers in childcare are low and sedentary time high. The Supporting Physical Activity in the Childcare Environment (SPACE) intervention had three components: 1. portable play equipment; 2. staff training; and, 3. modified outdoor playtime (i.e., shorter, more frequent periods). This study aimed to examine the effectiveness of the SPACE intervention on preschoolers’ physical activity levels and sedentary time during childcare hours (compared to standard care).Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 74 publications
(59 reference statements)
5
95
1
Order By: Relevance
“…To date, a small number of randomised trials have been conducted specifically targeting childcare scheduling of physical activity opportunities, for example through the provision of more frequent or longer periods of outdoor free play . The study conducted by Razak and colleagues reported a similar level of implementation as found in the current study, with 58% (n = 127) of childcare services found to be currently implementing a continuous free play schedule during an assessment of eligibility.…”
Section: Discussionsupporting
confidence: 61%
“…To date, a small number of randomised trials have been conducted specifically targeting childcare scheduling of physical activity opportunities, for example through the provision of more frequent or longer periods of outdoor free play . The study conducted by Razak and colleagues reported a similar level of implementation as found in the current study, with 58% (n = 127) of childcare services found to be currently implementing a continuous free play schedule during an assessment of eligibility.…”
Section: Discussionsupporting
confidence: 61%
“…Previously used combination interventions, which include both environmental and educational interventions, have also had mixed results. No response was noted in PA or step count in preschoolers in two studies (Finch et al, ; Tucker et al, ). However, Engelen et al () reported an increase in MVPA and total PA ( p = .006 & p = .002, respectively) among preschoolers with a combination intervention that added loose materials, such as crash mats, weighed boxes, and milk crates to the playground and an educational intervention for parents, teachers, and staff.…”
Section: Discussionmentioning
confidence: 97%
“…However, preschool children may not be getting the recommended daily amount or intensity (Tucker et al, ). Measuring PA objectively via accelerometers, results from two studies found U.S. preschool children spent more than 60 percent of the time in light activity (Hnatiuk, Salmon, Hinkley, Okely, & Trost, ), and more than 6 hr each day being sedentary with only about 15 min per day in moderate‐to‐vigorous PA (MVPA; Katapally & Muhajarine, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials were aligned with the PA cards to enable all preschools to perform the activities described on the cards. The box contained a variety of materials that could promote PA both indoors and outdoors, such as bean bags, hoops, balls, sidewalk chalk, and clothespins [59]. In addition, an assessment of preschool-specific needs for materials was performed in order to provide these additional materials (e.g., stepping-stones or foam blocks).…”
Section: Preschool-based Componentmentioning
confidence: 99%